227k views
2 votes
Can anyone help me solve this function?

Can anyone help me solve this function?-example-1
User Jasonmray
by
5.9k points

2 Answers

3 votes

We are given the following two equations:


f(x)=2x-6


g(x)=3x+9

To find (f+g)(x), we just add f(x) and g(x) and simplify:


(f+g)(x)=f(x)+g(x)


=2x-6+3x+9


=5x+3

Let me know if you need any clarifications, thanks!

User Antik
by
6.2k points
2 votes

Answer:

5x +3

Explanation:

f(x) = 2x-6

g(x) = 3x+9

(f+g) (x) = 2x-6+ 3x+9

Combine like terms

= 5x +3

User Gemantzu
by
6.3k points